Steel fiber reinforced concrete and concrete pipe piece
By forming a protective layer of phosphate and crosslinked silane on the surface of steel fibers, the problem of steel fiber reinforced concrete pipe sheets being easily rusted in high humidity environments is solved, and its service life and mechanical properties are extended in developed groundwater systems are achieved.
Patent Information
- Application Number
- CN202411715681.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Steel fiber reinforced concrete pipe sheets are prone to rust in high humidity or water-impregnated environments, resulting in a reduced service life in engineering environments with more developed groundwater systems.
By soaking the steel fibers in the first modified liquid and oscillating with ultrasonic waves, a phosphate protective layer is formed, and then soaking in the second modified liquid to form a crosslinked silane protective layer, thereby improving the alkali corrosion resistance of the steel fibers and the bonding strength with concrete.
Effectively prevent steel fibers from rusting, improve the service life of concrete in wet or groundwater systems, and improve its mechanical properties.
Smart Images

Figure CN119528510A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to construction engineering, and in particular to a steel fiber reinforced concrete and a concrete pipe segment. Background Art
[0002] Concrete segments are a type of prefabricated concrete parts, which are often used to be installed on the wall of a tunnel when a shield machine is used to dig during the construction of a large pipeline or tunnel. Due to the needs of this project, high compressive and flexural strengths are required for concrete segments, so steel fibers are added to existing concrete segments to enhance their strength.
[0003] Feedback from sample test results during actual application and engineering processes shows that steel fibers in steel fiber reinforced concrete samples are prone to rust in high humidity or water-soaked environments, and the durability test strength retention rate of steel fiber reinforced concrete samples is lower than that in dry environments. It is foreseeable that the service life of steel fiber reinforced concrete segments will be reduced in engineering environments with a more developed groundwater system and a high groundwater content.
[0004] Therefore, for such target projects, how to improve the service life of steel fiber reinforced concrete segments in engineering environments with relatively developed groundwater systems and high groundwater content is a real demand and research and development need. Summary of the invention
[0005] In order to improve the service life of steel fiber reinforced concrete segments in engineering environments with relatively developed groundwater systems and high groundwater content, a steel fiber reinforced concrete and concrete segments are provided.
[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A steel fiber reinforced concrete comprising the following raw materials in parts by weight: Aggregate 500-535 parts, 280-320 parts of sand, 170-200 parts of fly ash, 300-340 parts of water, 270-300 parts of cement, 20-27 parts of modified steel fiber; The modified steel fiber is obtained by surface modification of the steel fiber; The steel fiber surface modification method is as follows: S1: soaking the steel fiber in the first modified liquid and applying ultrasonic vibration for 30 minutes; S2: After the soaking treatment, the samples are fished out and dried, and then soaked in the second modification solution for 5 hours; The first modified liquid includes water, aluminum dihydrogen phosphate, and sodium lauryl sulfate, wherein the mass ratio of water, aluminum dihydrogen phosphate, and sodium lauryl sulfate is 90:30:3.4; Therefore, the second modified liquid is obtained by mixing water, ethanol and polysiloxane monomers, wherein the mass ratio of water, ethanol and polysiloxane monomers is 4:2:2.
[0007] By adopting the above technical solution, the steel fiber is treated with the first modifying liquid, and a phosphate protective layer of phosphate deposition is formed on the surface of the steel fiber. Then, the steel fiber is treated with the second modifying liquid, and a cross-linked silane protective layer formed by cross-linked silane is attached to the surface of the steel fiber again. The phosphate protective layer deposited by phosphate can effectively prevent the surface of steel fiber from rusting due to the galvanic reaction caused by contact with water and alkaline substances in concrete; The cross-linked silane protective layer formed by the cross-linked silane can protect the phosphate protective layer from being worn during the mixing process of the concrete raw materials, and can also enhance the wetting effect of the modified steel fiber with water and improve the bonding strength between the modified steel fiber and the concrete gel material. This increases the service life of the steel fiber reinforced concrete in a humid underground environment or an underground environment with a developed groundwater system, and also improves the mechanical properties of the steel fiber reinforced concrete.
[0008] Optionally, the temperature of the first modified treatment liquid in S1 is 28°C.
[0009] By adopting the above technical scheme, the phosphate protective layer formed on the steel fiber after being treated with the first modified treatment liquid is formed more dense and complete, and the alkali corrosion resistance of the steel fiber is better, thereby increasing the service life of the steel fiber reinforced concrete in a humid underground environment or an underground environment with a developed groundwater system.
[0010] Optionally, the polysiloxane-based silane monomer is propyltriethoxysilane.
[0011] By adopting the above technical scheme, the cross-linked silane protective layer formed is denser, has better protection effect on the phosphate protective layer, and has better effect on enhancing the bonding strength between the modified steel fiber and the concrete gel material. The obtained steel fiber reinforced concrete has a longer service life in a humid underground environment or an underground environment with a developed groundwater system, and has better mechanical properties.
[0012] Optionally, the first modified liquid further includes emulsified and dispersed castor oil, and the mass ratio of the castor oil to water is 0.8:90.
[0013] By adopting the above technical scheme, emulsified and dispersed castor oil is also added to the first modified liquid. The castor oil will demulsify during the modification process and adhere to the phosphate protective layer to temporarily protect the phosphate protective layer, thereby preventing the local phosphate protective layer from being loose or broken during the scooping process and causing rust during the drying process. This avoids the formation of rust spots on the modified steel fiber during the preparation process as much as possible, and prevents the rust spots on the modified steel fiber from becoming initiation points when in contact with an alkaline water environment, causing the rust to intensify.
[0014] Optionally, the composition further comprises 2.3 to 3.5 parts of a water reducing agent.
[0015] By adopting the above technical solution, the mixing performance of concrete can be improved, which helps to evenly disperse the modified steel fibers in the concrete and improve the mechanical properties of the concrete.
[0016] Optionally, the water reducing agent is magnesium lignin sulfonate.
[0017] By adopting the above technical solution, the two protective layers on the surface of the modified steel fiber are less damaged, thereby improving the service life of the steel fiber reinforced concrete in a humid underground environment or an underground environment with a developed groundwater system.
[0018] Optionally, 0.1 to 0.13 parts of hydrogenated rosin ester powder are also included.
[0019] By adopting the above technical scheme, hydrogenated rosin ester powder can play a lubricating effect in the process of mixing raw materials for concrete, reduce the wear between aggregate and sand on modified steel fibers, and improve the protective effect of phosphate protective layer and cross-linked silane protective layer. On the other hand, during the concrete curing process, hydrogenated rosin ester powder can absorb heat and soften or even change phase to absorb hydration heat, reduce the peak value of hydration heat, and reduce the corrosion effect of modified steel fibers during the concrete curing process.
[0020] The above second invention objective of the present invention is achieved through the following technical solutions: A steel fiber reinforced concrete pipe segment is formed by pouring the above concrete into a steel frame.
[0021] By adopting the above technical solution, the concrete pipe segment has a long service life and good durability when used in an engineering environment with a relatively developed groundwater system and a high groundwater content.
[0022] In summary, this application has at least the following beneficial effects: 1. The steel fiber is modified to form a phosphate protective layer and a cross-linked silane protective layer. The phosphate protective layer can effectively prevent the surface of the steel fiber from rusting due to the galvanic cell reaction caused by contact with water and alkaline substances in the concrete. The cross-linked silane protective layer can protect the phosphate protective layer from being worn during the mixing process of the concrete raw materials, and can enhance the infiltration effect of the modified steel fiber with water, and improve the bonding strength between the modified steel fiber and the concrete gel material; thereby improving the service life of the steel fiber reinforced concrete in a humid or underground environment with a developed groundwater system, and also improving the mechanical properties of the steel fiber reinforced concrete; 2. Emulsified and dispersed castor oil is also added to the first modified liquid. The castor oil will demulsify during the modification process and adhere to the phosphate protective layer to temporarily protect the phosphate protective layer, so as to avoid the local phosphate protective layer from being not dense or being broken during the scooping process and causing rust during the drying process, thereby avoiding the formation of rust spots on the modified steel fiber during the preparation process as much as possible, and preventing the rust spots on the modified steel fiber from becoming initiation points when the modified steel fiber contacts the alkaline water environment, causing the rust to intensify; 3. Hydrogenated rosin ester powder is also added to the raw materials of concrete, which can play a lubricating role in the process of mixing the raw materials of concrete, reduce the wear between aggregates and sand on modified steel fibers, and improve the protective effect of phosphate protective layer and cross-linked silane protective layer. On the other hand, during the concrete curing process, hydrogenated rosin ester powder can absorb heat, soften or even change phase, and then absorb hydration heat, reduce the peak value of hydration heat, and reduce the corrosion of modified steel fibers during the concrete curing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the steel fiber reinforced concrete segment structure.
[0024] Reference numerals: 1. Steel skeleton; 2. Concrete casting body. DETAILED DESCRIPTION
[0025] raw material The steel fiber is a milled steel fiber commercially available from Shandong Hongju Engineering Materials Co., Ltd., with a length of 35 mm, a width of 3 mm, and a thickness of 0.5 mm.
[0026] Aluminum dihydrogen phosphate, sodium lauryl sulfate, castor oil, ethanol, propyltriethoxysilane and n-octyltriethoxysilane are all commercially available industrial grade products.
[0027] The aggregate is crushed stone, and the particle size distribution is 5-6cm, 2-3cm, 0.5-1cm, and the mass ratio is 2:4:3.
[0028] The sand is natural river sand with a particle size of 0.5 to 0.8 mm.
[0029] The fly ash is first-grade fly ash from power plants, with a particle size of 200 mesh, a melting point of 1300℃ and a density of 2.65g / cm3.
[0030] The cement is 42.5 ordinary Portland cement.
[0031] Water reducers include magnesium lignin sulfonate and Sika -530P polycarboxylate water reducer, both are commercially available products.
[0032] The hydrogenated rosin ester powder is obtained by melting and granulating commercially available hydrogenated rosin ester, and has a particle size of 100±10 μm.
[0033] Preparation Example 1 A modified steel fiber is obtained by modifying steel fiber. The modification method is as follows: S1: Soak the steel fiber in the first modification liquid at 28°C and add ultrasonic vibration for 30 minutes; S2: Soak the steel fiber treated by S1, pick it up and dry it, and then soak it in the second modification liquid at 25°C for 5 hours, pick it up and dry it after soaking.
[0034] The first modified liquid is obtained by mixing water, aluminum dihydrogen phosphate, sodium lauryl sulfate and castor oil to uniformly emulsify the castor oil, wherein the mass ratio of water, aluminum dihydrogen phosphate, sodium lauryl sulfate and castor oil is 90:30:3.4:0.8.
[0035] The second modified liquid is obtained by mixing water, ethanol and polysiloxane monomer, wherein the mass ratio of water, ethanol and polysiloxane monomer is 4:2:2; and the polysiloxane monomer is propyltriethoxysilane.
[0036] Preparation Example 2 A modified steel fiber, which differs from Preparation Example 1 in that the temperature of the first modifying liquid during immersion in S1 is 22°C.
[0037] Preparation Example 3 A modified steel fiber, which differs from Preparation Example 1 in that the temperature of the first modifying liquid during immersion in S1 is 35°C.
[0038] Preparation Example 4 A modified steel fiber, which differs from Preparation Example 1 in that the polysiloxane-based silane monomer in the second modified liquid in S2 is n-octyltriethoxysilane.
[0039] Preparation Example 5 A modified steel fiber, which is different from Preparation Example 1 in that the first modified liquid in S2 is a mixture of water, aluminum dihydrogen phosphate, and sodium lauryl sulfate, wherein the mass ratio of water, aluminum dihydrogen phosphate, and sodium lauryl sulfate is 90:30:3.4.
[0040] Preparation Example 6 A modified steel fiber is obtained by modifying steel fiber. The modification method is as follows: S1: The steel fiber is immersed in the first modified liquid at 28°C and subjected to ultrasonic vibration for 28 minutes. After the immersion treatment, the steel fiber is fished out and dried.
[0041] The first modified liquid is obtained by mixing water, aluminum dihydrogen phosphate, sodium lauryl sulfate and castor oil to uniformly emulsify the castor oil, wherein the mass ratio of water, aluminum dihydrogen phosphate, sodium lauryl sulfate and castor oil is 90:30:3.4:0.8.
[0042] Preparation Example 7 A modified steel fiber is obtained by modifying steel fiber. The modification method is as follows: S1: Soak the steel fiber in the second modified liquid for 5.5 hours, and then fish out and dry it.
[0043] The second modified liquid is obtained by mixing water, ethanol and polysiloxane monomer, wherein the mass ratio of water, ethanol and polysiloxane monomer is 4:2:2; and the polysiloxane monomer is propyltriethoxysilane.
[0044] Example 1 The invention discloses steel fiber reinforced concrete, whose raw materials include aggregate, sand, fly ash, water, cement, modified steel fiber, water reducing agent and hydrogenated rosin ester powder.
[0045] The modified steel fiber was prepared in Preparation Example 1. The water reducing agent was magnesium lignin sulfonate.
[0046] The preparation method of steel fiber reinforced concrete is as follows: 320 kg of water and 3.2 kg of water reducing agent were mixed evenly to obtain production water, and 300 kg of sand and 0.12 kg of hydrogenated rosin ester powder were mixed evenly to obtain production sand; Evenly mix production water, production sand, 525 kg aggregate, 185 kg fly ash, and 286 kg cement to obtain a mixture; Then, 25.7 kg of modified steel fiber was added into the mixture and mixed evenly to obtain steel fiber reinforced concrete.
[0047] Example 2 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 2.
[0048] Example 3 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 3.
[0049] Example 4 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 4.
[0050] Example 5 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 5.
[0051] Example 6 A steel fiber reinforced concrete, which is different from Example 1 in that the water reducing agent is a polycarboxylic acid water reducing agent, specifically Sika of the same mass -530P polycarboxylate water reducer.
[0052] Example 7 The invention discloses steel fiber reinforced concrete, whose raw materials include aggregate, sand, fly ash, water, cement, modified steel fiber and hydrogenated rosin ester powder.
[0053] The modified steel fiber was prepared in Preparation Example 1. The water reducing agent was magnesium lignin sulfonate.
[0054] The preparation method of steel fiber reinforced concrete is as follows: 300 kg of sand and 0.12 kg of hydrogenated rosin ester powder were mixed evenly to obtain production sand; The production sand, 320 kg of water, 525 kg of aggregate, 185 kg of fly ash and 286 kg of cement are uniformly mixed to obtain a mixture; Then, 25.7 kg of modified steel fiber was added into the mixture and mixed evenly to obtain steel fiber reinforced concrete.
[0055] Example 8 The invention discloses a steel fiber reinforced concrete, whose raw materials include aggregate, sand, fly ash, water, cement, modified steel fiber and water reducing agent.
[0056] The modified steel fiber was prepared in Preparation Example 1. The water reducing agent was magnesium lignin sulfonate.
[0057] The preparation method of steel fiber reinforced concrete is as follows: Mix 320 kg of water and 3.2 kg of water reducing agent to obtain production water; The production water, 300 kg of sand, 525 kg of aggregate, 185 kg of fly ash and 286 kg of cement are uniformly mixed to obtain a mixture; Then, 25.7 kg of modified steel fiber was added into the mixture and mixed evenly to obtain steel fiber reinforced concrete.
[0058] Example 9 A steel fiber reinforced concrete is distinguished by different amounts of raw materials, specifically as follows: 500 kg aggregate, 280 kg sand, 170 kg fly ash, 300 kg water, 270 kg cement, 20 kg modified steel fiber, 2.3 kg water reducer and 0.1 kg hydrogenated rosin ester powder.
[0059] Example 10 A steel fiber reinforced concrete is distinguished by the different amounts of raw materials, which are as follows: 535 kg of aggregate, 320 kg of sand, 200 kg of fly ash, 340 kg of water, 300 kg of cement, 27 kg of modified steel fiber, 3.5 kg of water reducing agent and 0.13 kg of hydrogenated rosin ester powder.
[0060] Comparative Example 1 The invention discloses concrete, whose raw materials include aggregate, sand, fly ash, water, cement, water reducing agent and hydrogenated rosin ester powder.
[0061] The water reducing agent is magnesium lignin sulfonate.
[0062] The concrete preparation method is as follows: 320 kg of water and 3.2 kg of water reducing agent were mixed evenly to obtain production water, and 300 kg of sand and 0.12 kg of hydrogenated rosin ester powder were mixed evenly to obtain production sand; The production water, production sand, 525 kg of aggregate, 185 kg of fly ash and 286 kg of cement were uniformly mixed to obtain concrete.
[0063] Comparative Example 2 The invention discloses steel fiber reinforced concrete, whose raw materials include aggregate, sand, fly ash, water, cement, steel fiber, water reducing agent and hydrogenated rosin ester powder.
[0064] The steel fiber is unmodified steel fiber and the water reducing agent is magnesium lignin sulfonate.
[0065] The preparation method of steel fiber reinforced concrete is as follows: 320 kg of water and 3.2 kg of water reducing agent were mixed evenly to obtain production water, and 300 kg of sand and 0.12 kg of hydrogenated rosin ester powder were mixed evenly to obtain production sand; Evenly mix production water, production sand, 525 kg aggregate, 185 kg fly ash, and 286 kg cement to obtain a mixture; Then, 25.7 kg of steel fiber was added into the mixture and mixed evenly to obtain steel fiber reinforced concrete.
[0066] Comparative Example 3 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 6.
[0067] Comparative Example 4 A steel fiber reinforced concrete, which is different from Example 1 in that the modified steel fiber is prepared according to Preparation Example 7.
[0068] The concrete obtained from Examples 1 to 8 and Comparative Examples 1 to 4 was subjected to a compressive strength test, a flexural strength test, and a durability test in a simulated underground high humidity environment.
[0069] Compressive strength test: The test was carried out according to GB / T 50081-2019. The size of the concrete specimen was 100mm×100mm×100mm. The test was carried out after 28 days of curing.
[0070] Flexural strength test: According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete", the concrete specimen size is 100mm×100mm×400mm, and the test is carried out after 28 days of curing. The loading speed is 0.08MPa / s.
[0071] Simulated durability test in underground high humidity environment: According to GB / T 50081-2019, corresponding compression specimens and flexural specimens are made. After curing for 28 days, the specimens are immersed in pure water. After soaking for 12 hours, they are taken out of the water and placed in the air for 24 hours. After repeating the cycle of immersion and placement in the air for a total of 80 times, the specimens are placed in the air for 72 hours and then tested according to GB / T 50081-2019.
[0072] The test results are shown in Table 1.
[0073] Table 1. Concrete test results of Examples 1 to 10 and Comparative Examples 1 to 4 Combined with Table 1: Comparing the test results of Comparative Example 1 and Comparative Example 2, Comparative Example 2 added unmodified steel fibers compared with Comparative Example 1, and the compressive strength and flexural strength of Comparative Example 2 were improved compared with those of Comparative Example 1. However, in the simulated durability test of the underground high-humidity environment, the compressive strength and flexural strength of Comparative Example 1 did not show significant weakening, while in the simulated durability test of the underground high-humidity environment, the compressive strength and flexural strength of Comparative Example 2 showed a significant decrease, further verifying that the existing steel fiber reinforced concrete will have a decrease in strength performance and a shortened service life due to steel fiber corrosion in an engineering environment with a relatively developed groundwater system and a high groundwater content.
[0074] Combining Example 1 with Comparative Examples 2 to 4, it can be seen that the compressive strength and flexural strength of Example 1 are better than those of Comparative Examples 2 to 4. At the same time, in the simulated durability test of the underground high humidity environment, the compressive strength and flexural strength of Example 1 are significantly better than those of Comparative Examples 2 to 4. Therefore, the modified steel fiber used in this application is treated with the first modifying liquid, and a phosphate protective layer of phosphate deposition is attached to the surface of the steel fiber, and then treated with the second modifying liquid, and a cross-linked silane protective layer formed by cross-linked silane is attached to the surface of the steel fiber again; the phosphate protective layer of phosphate deposition can effectively prevent the surface of the steel fiber from rusting due to the galvanic reaction caused by contact with water and alkaline substances in concrete; the cross-linked silane protective layer formed by cross-linked silane can protect the phosphate protective layer from being worn during the mixing process of concrete raw materials, and on the other hand, it can enhance the wetting effect of the modified steel fiber and water, and improve the bonding strength between the modified steel fiber and the concrete gel material; thereby improving the service life of the steel fiber reinforced concrete in a humid or underground environment with a developed groundwater system, and also improving the mechanical properties of the steel fiber reinforced concrete.
[0075] In the present application, when the modified steel fiber is treated with the first modification treatment liquid, its immersion treatment temperature affects the density of the phosphate protective layer. By comparing Examples 1 to 3, it can be seen that the compressive strength and flexural strength of Example 1 are better than those of Examples 2 to 3. At the same time, in the durability test simulated in a simulated underground high-humidity environment, the compressive strength and flexural strength of Example 1 are significantly better than those of Examples 2 to 3. Therefore, the temperature of the first modification treatment liquid in the present application is preferably 28°C.
[0076] By comparing Example 1 and Example 4, it can be seen that the compressive strength and flexural strength of Example 1 are better than those of Examples 2 to 3. At the same time, in the simulated underground high-humidity environment simulated durability test, the compressive strength and flexural strength of Example 1 are significantly better than those of Examples 2 to 3. Therefore, the second modified treatment liquid uses propyltriethoxysilane as a polysiloxane silane monomer, and the cross-linked silane protective layer formed is denser, has a better protective effect on the phosphate protective layer, and has a better effect on enhancing the bonding strength between the modified steel fiber and the concrete gel material. The resulting steel fiber reinforced concrete has a longer service life and better mechanical properties in a humid underground environment or an underground environment with a developed groundwater system.
[0077] In combination with Example 1 and Example 5, the first modification treatment liquid used for the modified steel fiber used in Example 1 contains emulsified castor oil, which can adhere to the phosphate protective layer during the first modification treatment liquid treatment, and temporarily protect the phosphate protective layer to avoid the local phosphate protective layer from being loose or broken during the scooping process and causing corrosion during the drying process. This avoids the formation of rust spots on the modified steel fiber during the preparation process as much as possible, and prevents the rust spots on the modified steel fiber from becoming initiation points when in contact with the alkaline water environment, causing the rust to intensify. Therefore, the compressive strength and flexural strength of Example 1 are better than those of Example 5. At the same time, in the simulated underground high-humidity environment simulated durability test, the compressive strength and flexural strength of Example 1 are significantly better than those of Example 5.
[0078] Combining Example 1 and Examples 6 to 7, it can be seen that Example 1 and Example 6 further add a water reducer to the raw materials of concrete compared to Example 7. The compressive strength and flexural strength of Example 1 and Example 6 are better than those of Example 7. At the same time, in the simulated durability test of the underground high humidity environment, the compressive strength and flexural strength of Example 1 and Example 6 are better than those of Example 7. Therefore, adding a water reducer to the concrete raw materials in this application can improve the mixing performance of the concrete, help the modified steel fiber to be mixed evenly and dispersed in the concrete, and improve the mechanical properties of the concrete.
[0079] In addition, the compressive strength and flexural strength of Example 1 are better than those of Example 6. At the same time, in the simulated durability test of the underground high humidity environment, the compressive strength and flexural strength of Example 1 are better than those of Example 6. Therefore, it is better to use magnesium lignin sulfonate as the water reducer of the present application.
[0080] Comparing Example 1 and Example 8, Example 1 further adds hydrogenated rosin ester powder to the concrete raw materials compared with Example 8. The hydrogenated rosin ester powder can play a lubricating effect in the mixing and preparation process of the raw materials of the concrete, reduce the wear between the aggregate and the sand on the modified steel fiber, and improve the protective effect of the phosphate protective layer and the cross-linked silane protective layer. On the other hand, during the concrete curing process, the hydrogenated rosin ester powder can absorb heat and soften or even change phases to absorb hydration heat, reduce the hydration heat peak, and reduce the corrosion of the modified steel fiber during the concrete curing process. Therefore, the compressive strength and flexural strength of Example 1 are better than those of Example 8. At the same time, in the simulated underground high-humidity environment simulated durability test, the compressive strength and flexural strength of Example 1 are better than those of Example 8.
[0081] In addition, the present application has other preferred embodiments 9 to 10, from which it can be seen that the mass ratio of aggregate, sand, fly ash, water, cement, modified steel fiber, water reducer, and hydrogenated rosin ester powder in the steel fiber reinforced concrete of the present application is controlled within the range of (500-535):(280-320):(170-200):(300-340):(270-300):(20-27):(2.3-3.5):(0.1-0.13), so that concrete with a long service life can be obtained in an engineering environment with a relatively developed groundwater system and a high groundwater content.
[0082] Embodiment 11 As attached Figure 1 As shown, a steel fiber reinforced concrete pipe segment is in the form of a sheet, and its cross section in the vertical length direction is in the shape of a fan ring.
[0083] The concrete pipe segment has a steel skeleton 1 inside and a concrete casting body 2 outside. The steel skeleton is placed in a mold and then steel fiber reinforced concrete is cast, and then cured. The steel fiber reinforced concrete is one of Examples 1-10.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as the modifications are within the scope of protection required by the present application, they shall be protected by the patent law.
Claims
1. A steel fiber reinforced concrete, characterized in that: Including the following raw materials by mass: Aggregate 500~535 parts, 280~320 parts of sand, 170~200 parts of fly ash, 300~340 parts of water, 270~300 parts of cement, Modified steel fiber 20-27 parts; The modified steel fiber is obtained by surface modification of the steel fiber; The steel fiber surface modification method is as follows: S1: soaking the steel fiber in the first modified liquid and applying ultrasonic vibration for 30 minutes; S2: After the soaking treatment, the samples are fished out and dried, and then soaked in the second modification solution for 5 hours; The first modified liquid includes water, aluminum dihydrogen phosphate, and sodium lauryl sulfate, wherein the mass ratio of water, aluminum dihydrogen phosphate, and sodium lauryl sulfate is 90:30:3.4; Therefore, the second modified liquid is obtained by mixing water, ethanol and polysiloxane monomers, wherein the mass ratio of water, ethanol and polysiloxane monomers is 4:2:
2.
2. The steel fiber reinforced concrete according to claim 1, characterized in that: The temperature of the first reforming treatment liquid in S1 was 28°C.
3. The steel fiber reinforced concrete according to claim 1, characterized in that: The polysiloxane-based silane monomer is propyltriethoxysilane.
4. The steel fiber reinforced concrete according to claim 1, characterized in that: The first modified liquid also includes emulsified and dispersed castor oil, and the mass ratio of the castor oil to water is 0.8:
90.
5. The steel fiber reinforced concrete according to claim 1, characterized in that: The invention also includes 2.3 to 3.5 parts of a water reducing agent.
6. The steel fiber reinforced concrete according to claim 1, characterized in that: The water reducing agent is magnesium lignin sulfonate.
7. The steel fiber reinforced concrete according to claim 1, characterized in that: It also includes 0.1 to 0.13 parts of hydrogenated rosin ester powder.
8. A steel fiber reinforced concrete segment, characterized in that: The method is obtained by pouring the concrete according to any one of claims 1 to 7 on a steel frame.